Pulmonary tuberculosis and immunological profile of HIV/AIDS patients in Far West Nepal - Bohara, Madan Singh (Journal of Kathmandu Medical College, 2014)
Background: Tuberculosis is itself a major public health problem in Nepal and the emergence HIV further complicated the issue. Tuberculosis is the most common cause of death among HIV/AIDS patients worldwide. Tuberculosis and HIV co-infection is associated with special diagnostic and ther apeutic challenges and constitutes an immense burden on healthcare system of heavily infected countries like Nepal. Objective: The objective of the study was to determine the prevalence of pulmonary tuberculosis and their immunologic profi les among HIV positive patients. Methods: A hospital based cross-sectional study was conducted from Januray 2012 to July 2012 among adult HIV-positive patients attending ART centers at Seti Zonal Hospital and Mahakali Zonal Hospital. Clinical and laboratory investigations including Acid Fast staining and culture were used to identify tuberculosis cases. Blood samples were collected to determine CD4+ lymphocyte count. A structured questionnaire was used to collect socio-demographic characteristics of study participants. The data was entered and analysed using SPSS version 16 software. Results: A total of 103 HIV positive participants were enrolled. Five (4.9%) of the study participants (three females and two males) were found to have pulmonary tuberculosis. Majority [4(80%)] of TB-HIV co-infection was found in 21-40 years age group. Similarly four (80%) of them were illiterate. Among five TB cases only two cases were detected by direct microscopy. In general it was observed that various clinical manifestations such as cough, chest pain, weight loss, loss of appetite etc. are more common in TB co-infected HIV patients in comparison to non-co-infected counterparts. Similarly, higher percentage of TB cases were seen in patients with low CD4+ count (<500/mm3). Conclusions: We found high prevalence of tuberculosis-HIV co-infection. More such cases were seen among those with low CD4+ cell count. Early detection of co-infection is very necessary to facilitate early ART initiation, thereby strengthening their immune status. DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10917 Journal of Kathmandu Medical College Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, page: 8-13